Nitrogen-potassium relationship for diagnosis of plant nutritional status and fertilization of the potato crop - Cogo, Clarissa Melo; Andriolo, Jerônimo Luiz; Bisognin, Dilson Antônio; Godoi, Rodrigo dos Santos; Bortolotto, Orcial Ceolin; da Luz, Gean Lopes (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to determine the maximum K dilution curve and the relationship with the N dilution curve, during growth and development of the potato crop, for nutritional diagnosis and fertilization purposes. Treatments consisted of nutrient solutions with K concentrations of 3.5, 5.5, 6.5, 8, and 9.5 mmol L-1. The completely randomized experimental design was adopted with four replications. Four plants were harvested, at weekly intervals, to quantify plant growth and to determine N and K tissue concentrations. The maximum K dilution curve was adjusted, and the maximum K uptake was determined, during crop growth and development. It was observed that maximum K concentrations might be estimated from critical N concentrations. Quantities of K fertilizers to be supplied to achieve a pre-fixed crop yield can be estimated from tissue N concentration.
Keywords: Solanum tuberosum; dilution; mineral nutrition; fertilization